The case of the missing mouse—developing cystic fibrosis drugs without using animals - Marshall, Lindsay J.; Conlee, Kathleen M. (Frontiers in Drug Discovery, 2024)
Creating and developing new drugs can take decades, costs millions of dollars, requires untold human effort and usually, takes thousands of animal lives. Despite regulators professing confidence in non-animal approaches and guidance documents that permit submission of non-animal data, toxicity testing is routinely carried out in animals, employing rodents (invariably mice) and non-rodents. However, extensive preclinical testing in animals is still no guarantee that drugs will be safe and/or effective. In fact, more than nine out of every ten drugs that appear safe from animal trials will fail when tested in people, often due to unexplained toxicity or a lack of efficacy. This paper will describe recent advances in drug development where non-animal approaches have been used, to explore how and where these could be applied more widely to revolutionize the drug development pipeline and accelerate the creation of safe and effective medicines. As one case study, we look at the small molecule channel modifiers developed to address the consequences of the mutated chloride channel in the fatal genetic condition, cystic fibrosis. We then take a closer look at where drug development could be accelerated by focusing on innovative, human biology-based testing methods. Finally, we put forward recommendations, targeting all stakeholders, including the public, that will be needed to put this into practice and enable drug development to become more efficient - focusing on human-biology based testing and cutting out the middle-mouse.